2020
DOI: 10.1109/access.2020.2968583
|View full text |Cite
|
Sign up to set email alerts
|

Economic Dispatch of Combined Heat and Power Energy Systems Using Electric Boiler to Accommodate Wind Power

Abstract: It is of significant economic value to use an electric boiler to coordinate the heating network and power grid to reduce wind curtailment during heating supply seasons in the north area. This paper presents an optimal economic dispatching model of combined heat and power energy systems to minimize the total operation cost and wind curtailment by using electric boilers. The proposed model comprehensively considers the thermal characteristics of buildings and the constraints of electric and thermal power balanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…FANG et al [13] proposed to use electric boiler (EB) with heat storage to participate in peak load regulation of power grid, so that the power grid can accommodate more wind power generation. LIANG et al [14] and LIU et al [15] respectively analyzed the improvement effect of CHP unit and electric boiler equipped with heat storage device on the wind power accommodation capacity of integrated heat-power system. Through calculation, it showed that heat storage device and electric boiler can improve the wind power accommodation capacity and reduce coal consumption.…”
Section: Index and Sets Nmentioning
confidence: 99%
“…FANG et al [13] proposed to use electric boiler (EB) with heat storage to participate in peak load regulation of power grid, so that the power grid can accommodate more wind power generation. LIANG et al [14] and LIU et al [15] respectively analyzed the improvement effect of CHP unit and electric boiler equipped with heat storage device on the wind power accommodation capacity of integrated heat-power system. Through calculation, it showed that heat storage device and electric boiler can improve the wind power accommodation capacity and reduce coal consumption.…”
Section: Index and Sets Nmentioning
confidence: 99%
“…To test the performance of the ADRC system in tracking the main steam temperature command signal, the paper added a unit step signal to the main steam temperature command signal input terminal to investigate the rapidity, accuracy and robustness of the system in tracking the given value [8].…”
Section: Simulation Experiments and Analysismentioning
confidence: 99%
“…Since the main regulator adopts an active disturbance rejection controller, there is currently no effective method for determining the parameter setting of the state error feedback controller [9]. Therefore, combined with the simulation experiment, the paper gives the coefficients of the non-linear state error feedback controller: q 1 = 450, q 2 = 27000, q 3 = 1.65 × 10 6 , q 4 = 2.35 × 10 7 , q 5 = 2.35 ×10 8 . The secondary regulator P adopts a pure proportional regulator, and the proportional coefficient is kp 2 = 8.…”
Section: Simulation Under 100% Load Conditionmentioning
confidence: 99%
“…where Ui,min and Uimax are the maximum and minimum of node i voltage; Pij,max and Pijmin are the maximum and minimum of power on branch ij; PGi,max and PGi,min are the maximum and minimum of generator active power output; QGi,max and QGi,min are the maximum and minimum of generator reactive power; PGi,up and PGi,down are the upper and lower ramp limits of generator output. Equations (5) represent nodal voltage constraint, line power constraint, generator active and reactive power output constraints, and generator active power output ramp constraints, respectively.…”
Section: B Constraintsmentioning
confidence: 99%
“…Dynamic optimal power flow (DOPF) is one of the key problems in power system economic dispatch and safe operation [1]. The DOPF problem is a typical mixed integer nonlinear programming problem essentially [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%